Estudos de QSAR-2D em quinolina metanol com atividade antimalárica frente ao Plasmodium falciparum - Duarte, Carla dos Santos (2012)
An analysis of 2D-QSAR was realized in twelve two quinoline methanol substituted in position 4 with antimalarial activity against the Plasmodium falciparum. The semi-empirical quantum methods AM1 and RM1 were used to calculate the geometry and some molecular properties. The DRAGON program was also used to produce descriptors and MobyDigs was used to select descriptors and build QSAR models. The best obtained from QSAR models used multiple linear regression. The model with 12 composed have descriptors, and G3v R2e, resulting in r2 = 0.90, q2 = 0.79 and q2boot = 0.72. The validation was performed on RQK fitness functions. It was shown that the QSAR model satisfies all the criteria required for validation, indicating that the regression model is acceptable. The external validation was performed with the exclusion of compounds AAQM_4, AAQM_7 and AAQM_11. The new model was generated as descriptors, and Mor28u MPC05, with r2 = 0.98, q2 = 0.97 and q2boot = 0.94. Considered valid for the functions RQK adjustment. Keywords: malaria, QSAR, quinoline methanol.